THE CONCEPTION OF PURE FANTASTIC IN MODERN UKRAINIAN LITERATURE (ON THE MATERIAL OF WORKS BY M. AND S. DIACHENKO AND YA. MELNYK) - Khorob, S. S. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Word, 2020)
The article investigates the peculiarities of the fantastic works by modern Ukrainian writers Maryna and Serhii Diachenko «Pechera» («The Cave») and «Chomu ya ne vtomliuiusia zhyty» («Why I Never Tire of Living») by Yaroslav Melnyk. It argues that pure fantastic is an equal genre of the fantastic literature along with fantasy and science fiction.